2019
DOI: 10.4049/jimmunol.1801668
|View full text |Cite
|
Sign up to set email alerts
|

Human Eosinophils Express a Distinct Gene Expression Program in Response to IL-3 Compared with Common β-Chain Cytokines IL-5 and GM-CSF

Abstract: Despite recent advances in asthma management with anti–IL-5 therapies, many patients have eosinophilic asthma that remains poorly controlled. IL-3 shares a common β subunit receptor with both IL-5 and GM-CSF but, through α-subunit–specific properties, uniquely influences eosinophil biology and may serve as a potential therapeutic target. We aimed to globally characterize the transcriptomic profiles of GM-CSF, IL-3, and IL-5 stimulation on human circulating eosinophils and identify differences in gene expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 48 publications
(55 reference statements)
0
16
0
Order By: Relevance
“…First, GM-CSF participates in the resolution of in ammation, and IL-3 and IL-5 may also have such properties [10]. In addition, It has been reported that GM-CSF and IL-5 stimulation increase eosinophil gene expression [22]. Similar to IL-5, another cytokines including IL-3 and GM-CSF cytokines are produced as part of the Th2 in ammatory response and are crucial to eosinophil development and function.…”
Section: Discussionmentioning
confidence: 99%
“…First, GM-CSF participates in the resolution of in ammation, and IL-3 and IL-5 may also have such properties [10]. In addition, It has been reported that GM-CSF and IL-5 stimulation increase eosinophil gene expression [22]. Similar to IL-5, another cytokines including IL-3 and GM-CSF cytokines are produced as part of the Th2 in ammatory response and are crucial to eosinophil development and function.…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophils were purified from peripheral blood of healthy donors by negative selection (StemCell Technologies, Vancouver, Canada) 29 and pretreated with 10 ng/mL interleukin (IL) 5 for 48-72 hours. Eosinophils were then added at a 1:1 ratio to monolayers of active EoE fibroblasts cultured in 4-well slide chambers untreated or prestimulated with 50 ng/mL LIGHT for 24 hours.…”
Section: Fibroblast-eosinophil Coculture Modelmentioning
confidence: 99%
“…IL-3, IL-5, and GM-CSF have similar effects on eosinophil adhesion and comparable efficacy to induce eosinophil transmigration through a layer of epithelial cells via the β2 integrin [8]. Due to the abovementioned properties, IL-3, IL-5, and GM-CSF are considered as a potential target in asthma therapeutics [27]; however, IL-5 was selected as a priority target to reduce eosinophilia because it is highly specific for eosinophilic inflammation [28].…”
Section: Role Of Eosinophilopoietins On Eosinophils Functionsmentioning
confidence: 99%
“…The IL-5 receptor is fairly specific since it is only expressed on eosinophils and basophils, while receptors for IL-3 and GM-CSF are present on many haematopoietic cells [28]. Despite all three cytokines sharing a standard beta (β) chain receptor subunit, each differentially affects eosinophils biology due to alpha (α) chain subunit-specific properties [27]. The cytokines attach to their respective α-chain with low affinity (nanomolar); on the other hand, subsequent recruitment of the β-chain contributes to a conformational change to a great affinity (picomolar) binding complex [8].…”
Section: Role Of Eosinophilopoietins On Eosinophils Functionsmentioning
confidence: 99%
See 1 more Smart Citation